İtikadi Konularda Haber-i Vâhidin Delil Olma Meselesi ve Kevserî’nin Konuya Bakışı - (:unkn) unknown (My University, 2014)
Haber-i vâhidlerin itikadi konularda delil olması öteden beri tartışılan bir konudur. Cumhur ulema geliş yolu itibariyle zannîlik taşıdığından âhâd tarikle gelen hadislerin itikadda delil olmasını doğru bulmamıştır. Ehl-i hadis uleması ise haber-i vâhidlerin hem itikadi hem amelî konularda delil olacağı kanaatindedir. Bir kısım ulema da bazı karinelerle desteklenmiş haber-i vâhidlerin kesinlik taşıyacağını ve do- layısıyla itikadda da delil olabileceğini söylemişlerdir. XX. yüzyılın başlarında Mısıra yerleşen Osmanlının son Şeyhülislâm vekili Muhammed Zâhid el-Kevserî bulunduğu coğrafyadaki bazı Müslüman aydınların Hz. İsanın nüzûlü konusu bağlamında haber-i vâhidin itikadda delil olamaya- cağını iddia etmelerine karşı çıkmış ve bu konuda kitap ve makaleler yazmıştır. Ona göre haber-i vâhid sübûtu açısın- dan zannî olsa da itikad oluşturmaya yetecek bir bilgi vere- bilir. Zira inanmak kalbin amelidir. Haber-i vâhid amelî ko- nularda delil sayıldığına göre bu konuda da itibara alınması mümkündür. Ayrıca Buhârî-Müslim tarafından nakledilmiş olmak gibi ilave bir özelliğe sahip haberler de bazı âlimlere göre kesinlik taşımaktadır. Sonuçta Kevserî geçmişte ulema- nın itikadi konularla ilgili hadisleri derlemelerini ve akâid- kelâm kitaplarında her türlü hadisi kullanmalarını da delil getirerek haber-i vâhidden itikad oluşturmada yararlanıla- bileceği kanaatine varmıştır.

The authority of individual hadiths has long been debated in the Islamic literature. Majority of scholars argue that indivi- dual hadiths are not taken as evidence in theology because they yield only probable knowledge. Partisans of hadith, on the other hand, believe that individual hadiths can be evi- dence in both legal and theological matters. A third group of scholars maintain that individual hadiths supported by circumstantial evidence can provide certain knowledge and therefore become binding in matters of faith as well. Muhammad Zahid al-Kawthari, the deputy of the last Otto- man Shaykh al-Islam who settled in Egypt in the early 1900 s, penned books and articles in order to refute some Muslim intellectuals claim that individual hadiths have no capacity to be evidence in theology. For him, though the transmissi- on of individual hadiths is only probable, they can still yield knowledge strong enough to establish a theological princip- le because believing is the action of the heart; therefore they can be taken into account in theology just as they are con- sidered evidence in legal matters. Additionally, according to some scholars, reports that possess extra privileges such as being narrated by Bukhari or Muslim yield certainity. Thus, Kawthari has concluded that individual reports can be used to establish a theological principle by asserting that scholars of the past collected every type of theological traditions and contained them in their books on theology.
The Authority of Individual Hadiths in Theological Matters and Kawthari’s Approach to the Problem